Improvement of Visible Photodetection of Chemical Vapor Deposition-Grown MoS2 Devices via Graphene/Au Contacts - Yeongsik Hwa; Sang-Soo Chee (Sensors, 2022)
Two-dimensional (2D) molybdenum disulfide (MoS2) is a promising material for constructing high-performance visible photosensor arrays because of its high mobility and scale-up process. These distinct properties enable the construction of practical optoelectrical sensor arrays. However, contact engineering for MoS2 films is not still optimized. In this work, we inserted a graphene interlayer between the MoS2 films and Au contacts (graphene/Au) via the wet-transfer method to boost the device performance. Using graphene/Au contacts, outstanding electrical properties, namely field-effect mobility of 12.06 cm2/V∙s, on/off current ratio of 1.0 × 107, and responsivity of 610 A/W under illumination at 640 nm, were achieved. These favorable results were from the Fermi-level depinning effect induced by the graphene interlayer. Our results may help to construct large-area photonic sensor arrays based on 2D materials.